Voluntary and mandatory use of face mask by pedestrians in Guatemala City during the COVID-19 pandemic - Guerra-Centeno, Dennis; Burmester-Ruiz, Luisa; Guerra-Burmester, Paula; Guerra-Burmester, Dennis; Villatoro-Paz, Federico (Ciencia, Tecnología y Salud, 2020)
The COVID-19 pandemic has currently affected more than 200 countries and caused around four million cases. Face masks are recommended for preventing the contagion. The Guatemalan government issued a decree for the mandatory use of face masks in public places. In order to find out the frequency of voluntary and mandatory use of face masks by Guatemalans we conducted a case study divided in two episodes (pre and post mandatory use decree) by driving a 27.8 km car transect through 11 of the 22 zones of Guatemala City and observing the use of face mask by pedestrians walking on the sides of the transect. Pedestrians were visually classified by age category (children [< 12 years], juveniles [12-21 years], adults [21-65 years] and elders [> 65 years]) and gender. During the pre-decree observation, we registered 476 individuals using a face mask and 674 not using or using them improperly. During the post-decree observation, we registered 797 individuals using face mask and 211 not using or using them improperly. In general, the frequency of face mask use was higher in the post-decree sample. Males used masks less frequent than females, especially the elders and before the decree became mandatory. Although the mandatory use decree managed to increase the frequency of the use of the mask, there is a portion of the population that is not using it or that is using it improperly, so this should be considered by the health authorities who are dealing with the COVID-19 pandemic.